(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2022)
The COVID-19 pandemic from the beginning of 2020 to the end directly affected the health and general well-being of people with disabilities—the world’s largest minority, constituting approximately 15% of the world’s population. People with disabilities are more severely affected by the institutional barriers during the COVID-19 crisis. In Macedonia, there is no accurate data on the condition of people with disabilities during the COVID-19 pandemic. The aim of this study was to document the impact of COVID-19 on Macedonian persons with disabilities. According to this study, the primary source of support for people with disabilities was their families (72.3%). Friends were less pointed as a source of support (19.6%). From a total of 112 people with disabilities, included in this research, 41.1% answered that they had reduced social interaction due to the pandemic. In general, most people with disabilities stated that they were concerned about the additional cost of food and medicine and that they feared a possible infection with COVID-19.